A new species of Leptobrachium Tschudi, 1838 (Anura, Megophryidae) from Northeast India - Purkayastha, Jayaditya; Dutta, Dipankar; Gogoi, Jayanta; Sengupta, Saibal (Zootaxa, 2025)
A new species of Leptobrachium (Anura: Megophryidae) is described from Garbhanga Reserve Forest, Assam, India, based on an integrative taxonomic approach. Leptobrachium aryatium sp. nov. is a medium-sized species, with adult SVL of 49.0–55.4 mm in males and 53.2–61.65 mm in females. It is morphologically distinct from its congeners by having an obscured tympanum, a bicoloured iris with the top quarter fiery orange forming an inverted "V" shape and the rest black, and a spade-shaped inner metatarsal tubercle. Additional distinguishing features include a distinct supratympanic fold extending from behind the eye to the arm insertion, toe webbing formula: I 0–1 II 0–2 III 0–3 IV 3–1/2 V, and prominent black blotches on the dorsum and tibia. The ventrum is creamy to white with varying amounts of dark infusion, and the gular region exhibits a prominent black reticulation pattern. Phylogenetic analyses based on the mitochondrial 16S rRNA gene reveal that Leptobrachium aryatium sp. nov. forms a well-supported sister lineage to the clade comprising L. sylheticum and L. smithi, with genetic divergences of 2.0–2.3% and 3.7–4.3%, respectively. Acoustic analyses further distinguish Leptobrachium aryatium sp. nov. from its closest relatives, with differences in call duration, frequency range, and amplitude patterns.